2001
DOI: 10.1136/heart.86.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Nurse led shared care for patients on the waiting list for coronary artery bypass surgery: a randomised controlled trial

Abstract: Objective-To evaluate the eVectiveness of a nurse led shared care programme to improve coronary heart disease risk factor levels and general health status and to reduce anxiety and depression in patients awaiting coronary artery bypass grafting (CABG). Design-Randomised controlled trial. Setting-Community, January 1997 to March 1998. Study groups-98 (75 male) consecutive patients were recruited to the study within one month of joining the waiting list for elective CABG at Glasgow Royal Infirmary University NHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(192 citation statements)
references
References 32 publications
7
178
3
4
Order By: Relevance
“…The influence of socio-economic status is discussed later. It has previously been suggested that CAD risk factor management could be improved across the primary to secondary care interface as well as between the different professional groups looking after patients undergoing coronary artery bypass grafting [15]. We cannot confirm that this is occurring.…”
Section: Discussionmentioning
confidence: 81%
“…The influence of socio-economic status is discussed later. It has previously been suggested that CAD risk factor management could be improved across the primary to secondary care interface as well as between the different professional groups looking after patients undergoing coronary artery bypass grafting [15]. We cannot confirm that this is occurring.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to information in writing or by telephone, the patient can be informed at a preadmission clinic. Previous studies showed that preoperative anxiety was reduced in intervention groups of heart patients who had been to a preadmission clinic, compared with control groups who did not attend these clinics (Lindsay et al 1998, McHugh et al 2001. A preadmission clinic could also aim at identifying the patientsÕ mood, in order to be better able to support patients who need help, for instance when their operation is postponed or cancelled.…”
Section: Perceptions Of Waiting Timementioning
confidence: 99%
“…Firstly, although no previous study has reported from the Netherlands there have been reports of similar studies from Scotland, 2,3 and England. 4,5 Three of these demonstrated improvements in blood pressure control with nurse-led interventions, 2,3,5 while the other did not.…”
Section: Nurse-led Management Of Hypertensionmentioning
confidence: 96%
“…4,5 Three of these demonstrated improvements in blood pressure control with nurse-led interventions, 2,3,5 while the other did not. 4 The authors 1 conclude that their findings support the involvement of practice nurses in cardiovascular risk management.…”
Section: Nurse-led Management Of Hypertensionmentioning
confidence: 99%